Insights into the Intramolecular Properties of η6-Arene-Ru-Based Anticancer Complexes Using Quantum Calculations - Adebayo A. Adeniyi; Peter A. Ajibade (Journal of Chemistry)
The factors that determine the stability and the effects of noncovalent interaction on the η6-arene ruthenium anticancer complexes are determined using DFT method. The intramolecular and intra-atomic properties were computed for two models of these half-sandwich ruthenium anticancer complexes and their respective hydrated forms. The results showed that the stability of these complexes depends largely on the network of hydrogen bonds (HB), strong nature of charge transfer, polarizability, and electrostatic energies that exist within the complexes. The hydrogen bonds strength was found to be related to the reported anticancer activities and the activation of the complexes by hydration. The metal–ligand bonds were found to be closed shell systems that are characterised by high positive Laplacian values of electron density. Two of the complexes are found to be predominantly characterised by LMCT while the other two are predominately characterised by MLCT.